Handy purifier based on bacterial cellulose and Ca-montmorillonite composites for efficient removal of dyes and antibiotics. (15th October 2019) - Hu, Ying; Chen, Chuntao; Yang, Luyu; Cui, Jian; Hao, Qingli; Sun, Dongping
Highlights: An organic-inorganic composite (BC/Ca-MMT) was applied in water purification. PH considerably affected methylene blue and tetracycline adsorption performance. Simultaneous removal of the two model pollutants in simulated real water. The separation of the sample from adsorption medium could be achieved by hand. Abstract: Water purification has always being an imperative but challenging issue of our times. Here, we used an organic-inorganic material, i.e. bacterial cellulose (BC) and Ca-montmorillonite (Ca-MMT) composites to treat complex wastewater. The surface and inside of the BC/Ca-MMT was a microporous structure capable of providing abundant adsorption sites. We demonstrated the BC/Ca-MMT has superior removal efficiency towards methylene blue (MB) and tetracycline (TC). Typically, the sample showed significant uptake ability towards MB and TC with uptake characteristics of pseudo-second-order model and Langmuir isotherm model. More interestingly, in MB-TC binary system, the removal of the two contaminative species was hardly affected by other coexisting components. Meanwhile, the sample was ease of regeneration and kept stable reusability through consecutive four recycles. With more virtues, such as low cost and wide range of resources of the two raw materials, the BC/Ca-MMT is expected to be a promising versatile water purifier in sewage treatment.